Copper(II) complexes of arylhydrazone of 1H-indene-1,3(2H)-dione as catalysts for the oxidation of cyclohexane in ionic liquids - Tiago, Gonçalo A. O. (2019)
This research was founded by the Foundation for Science and Technology (FCT), grant PD/BD/106015/2014. The APC was funded by SFRH/BPD/90883/2012).